Impact of genetically improved fish species and technology on selected hatchery and fish production in Bangladesh - Islam, MS; Kohinoor, AHM; Rahman, MM; Haque, MM (International Journal of Agricultural Research, Innovation and Technology, 2017)
The study was carried out in IAPP commanding areas from July to September 2015. A total of 8 hatchery and 240 farmers were selected for this study from Rangpur and Barisal region. About 153% Tilapia production increased which was from 34 to 86 lakh, which was 148% in Rangpur district. Thai koi production was increased about 320% in Rangpur and it was 152% in Barisal. It was observed that, per hatchery Tilapia profit was Tk. 17.35 lakh and Tk. 17.18 lakh in Rangpur and Barisal, respectively. While, total profit was 3.9 times more for Thai koi in Rangpur and it was about 1.7 times more in Barisal after IAPP-BFRI project implementation. Impact of improved germplasm on grow out system was estimated. Finding shows that before IAPP-BFRI project the average harvesting weight of tilapia fish was 122g but after using IAPP-BFRI germplasm, it increased to 194g in Rangpur district. In case of Thai Koi, the harvesting weight gain was 26% in Rangpur district and it was statistically significant at 1% level. Survey results also show that per acre profit was only Tk.86671 for Tilapia farming before IAPP whereas it was increased to Tk. 234853 after IAPP-BFRI intervention. At the same time, profit from Thai Koi was increased about 189% after IAPPBFRI activities. Similarly, profit was increased about 86% in case of Pangus farming and this positive impact was statistically significant at 1% level. Therefore, it may conclude that, farmers can significantly increase Tilapia, Thai Koi and Pangus production as well as can maximize profit using IAPP technology. Int. J. Agril. Res. Innov. & Tech. 7 (1): 58-63, June, 2017